Impact of Television Advertising of Cosmetic Products on Consumer Behavior: With Reference to Sunsilk Shampoo - Pokharel, Prakash (KMC Research Journal, 2017)
The main objective of this research is to analyze the general impact of television advertising on consumer behavior with reference to Sunsilk Shampoo. Many people use advertising at some time in their life. Some may use it privately while others may use in business. And many people respond to advertisements. They enjoy the choices available to them in every sphere of life (Kotler, 1994:24). It is one of the major tools that companies use to persuade target buyers and publics to buy their products or services. In this scenario researcher takes Survey research design as a methodology. In this study media of advertising and impact of television advertising have been evaluated. Data used in this study are only primary in nature. The required data are collected through the questionnaire survey among the people of different age groups, gender, different education group etc. covering the consumer of urban area. According to the findings it can be concluded that majority of the people have television watching habits and out of them women are more curious in television then men which indicated that television advertisement is more popular means of advertisement.